A cross-coupling-annulation cascade from peri-dibromonaphthalimide to pseudo-rylene bisimides. Issue 11 (14th September 2016) - Seifert, Sabine; Schmidt, David; Würthner, Frank
Abstract : A novel synthetic strategy based on cascade C–C cross-coupling and C–H arylation afforded structurally unique polycyclic aromatics with desirable optical and redox properties. Abstract : Herein we report a synthetic method to annulate naphthalimide moieties at different positions of a pyrene core by a cascade reaction involving palladium-mediated Suzuki–Miyaura cross-coupling and direct C–H arylation affording a new class of rylene bisimides, which we term as pseudo -rylene bisimides. The Pd-mediated reactions of peri -dibromonaphthalimide and pyrene boronic acid esters lead exclusively to six-membered ring annulation by a cascade C–C bond formation, for which a mechanistic rationale is proposed. Depending on the molecular geometry of the new pseudo -rylene bisimides, their optical properties resemble those of zethrene or terrylene bisimides, or polycyclic aromatic hydrocarbons like coronenes. The structural integrity of this new type of pseudo -rylene bisimides was confirmed by single crystal X-ray analysis.